2013
DOI: 10.1523/jneurosci.5765-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Artemin, a Glial Cell Line-Derived Neurotrophic Factor Family Member, Induces TRPM8-Dependent Cold Pain

Abstract: Chronic pain associated with injury or disease can result from dysfunction of sensory afferents whereby the threshold for activation of pain-sensing neurons (nociceptors) is lowered. Neurotrophic factors control nociceptor development and survival, but also induce sensitization through activation of their cognate receptors, attributable, in part, to the modulation of ion channel function. Thermal pain is mediated by channels of the transient receptor potential (TRP) family, including the cold and menthol recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 67 publications
5
90
1
Order By: Relevance
“…S5). TRPM8 is the principle cold thermoreceptor in mammals, and we have shown that it is required for artemin-mediated cold allodynia (8,31). GFRα3 is expressed in one-half of TRPM8 + DRG neurons (8), but consistent with our transcript expression analysis, we observed no difference in the number of TRPM8-positive neurons between WT and Gfrα3 −/− mice (Fig.…”
Section: Significancesupporting
confidence: 85%
See 4 more Smart Citations
“…S5). TRPM8 is the principle cold thermoreceptor in mammals, and we have shown that it is required for artemin-mediated cold allodynia (8,31). GFRα3 is expressed in one-half of TRPM8 + DRG neurons (8), but consistent with our transcript expression analysis, we observed no difference in the number of TRPM8-positive neurons between WT and Gfrα3 −/− mice (Fig.…”
Section: Significancesupporting
confidence: 85%
“…NGF, protons, bradykinin, and histamine, to name a few, are all capable of potentiating TRPV1 responses (7,29,44,45) and responsible for the development of heat hyperalgesia. However, only artemin and NGF induce cold allodynia in a manner similar to that found after injury (8). Here, Fig.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations